2013
DOI: 10.1002/ceat.201200479
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of the Collision and Coalescence of Water Droplets in an Electric Field

Abstract: The coalescence of binary water droplets in oil exposed to an external electric field is simulated using a model including both electrostatic and hydrodynamic sections. Available mathematical models for electric dipole-dipole force are presented in the first part of the model. Volume of Fluid approach is applied in the second part of the model. The simulation results were in good agreement with the published experimental observations. The results indicated that an improvement in electrocoalescence speed could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…More recently, Takahashi 14 and, 2 years later, Creux et al 15 measured the zeta potential of air/water interfaces, confirming the analysis of Loeb 13 that an electrical double layer exists at a gas/liquid interface related to a dielectric constant. Collision and coalescence were analyzed and simulated by Mohammadi et al 16.…”
Section: Theorymentioning
confidence: 99%
“…More recently, Takahashi 14 and, 2 years later, Creux et al 15 measured the zeta potential of air/water interfaces, confirming the analysis of Loeb 13 that an electrical double layer exists at a gas/liquid interface related to a dielectric constant. Collision and coalescence were analyzed and simulated by Mohammadi et al 16.…”
Section: Theorymentioning
confidence: 99%
“…In view of the fact that several previous studies have demonstrated the feasibility of the VOF method on investigating the drop coalescence in the external flow field, the current mathematical model has the ability to numerically predict both the coalescence and the collision between the interacting drops in the shear flow [43][44][45]. Notably, herein, we concentrate on investigating the hydrodynamics of the collision between two drops which usually plays a considerable role in several practical applications including solvent extraction and emulsification [22].…”
Section: B Mathematical Modelmentioning
confidence: 99%
“…The approach process is mainly dominated by the electrostatic force and the drag force. The time for the approach process depends on not only the waveform and strength of electric field but also the droplet radius, the initial separation distance, the skew angle between the electric field and the central axis of two droplets, and fluid properties, such as viscosity and permittivity . When the initial separation distance is far greater than the droplet radius, the electrostatic force can be calculated by a point dipole model .…”
Section: Introductionmentioning
confidence: 99%